The Art of Illustrating the Impossible: Marcel Proust’s A la recherche du temps perdu through the eyes of Kees van Dongen - Vrielink, Charlotte (RELIEF - REVUE ÉLECTRONIQUE DE LITTÉRATURE FRANÇAISE, 2017)
Since the publication of Marcel Proust’s A la recherche du temps perdu (1913-1927), multiple artists have taken up the challenge of visualizing his modernist magnum opus. In this article, I will discuss the interpretation of Dutch artist Kees van Dongen, who created 77 illustrations for a luxury edition published by Gallimard in 1947. By looking at the way Van Dongen visualized different forms of art, I will argue that Van Dongen’s interpretation is more artistically interesting than has been asserted before, as there are many intertextual and even intermedial references and practices to be found in Van Dongen’s aquarelles.